Penetapan Parameter Spesifik Dan Non Spesifik Ekstrak Etanol Kulit Batang Kawista (Limonia Acidissima Groff) - Fenny Wiji Astuti; Tunik Saptawati; Anifatus Sa’adah; Ovikarini Ovikarini (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
Introduction : Indonesia is country that passed by the equator causing sunlight intensity increase that causes skin problems. Sunscreen is a cosmetic which used to protect skin from sun exposure. Kawista stem bark (Limonia acidissima Groff) has a flavonoid dan phenolic as UV protector. This study analyzed SPF values of ethanol extract, n-hexane fraction, etil acetate fraction, water fraction and sunscreen cream. Method : Spesific and non spesific standardization of ethanolic extract. Extraction using maceration method with 96% ethanol. The suncreen cream were made in 2% (F1), 4% (F2) and 6% (F3) concentration. Physical characteristics has tested include organoleptic, homogeneity, pH, dispersibility and adhesion and viscosity. Oneway ANOVA and kruskall wallis test statistic analysis. Oneway ANOVA and kruskall wallis test statistic analysis. Result : SPF values on F1 is 3,63 (minimal protection); F2 is 7,53 (Extra protection) and F3 is 15, 43 (Ultra protection). Conclusion : All three cream formula has a different significant SPF values (p < 0,05). The suncreen cream fulfilled the requirements of physical characteristics.